2013
DOI: 10.1111/sed.12047
|View full text |Cite
|
Sign up to set email alerts
|

Microbial dolomite in fresh water carbonate deposits

Abstract: This article reports evidence for biologically mediated precipitation of dolomite in a fresh water spring in the south‐east of Spain. Build‐ups in the spring consisted of calcite, minor dolomite, barite and gypsum crystals formed by the mineralisation of microbial biofilms and bryophytes. A detailed microscopic study, coupled with geochemical analysis of the dolomite‐precipitating biofilms, showed that dolomite crystals occurred in association with living coccoid micro‐organisms, providing strong evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…These deposits can be classified as thermogene deposits following Pentecost (2005) classification. δ 13 C values in hot-water travertine deposits are mainly controlled by physical (CO 2 degassing or water temperature) and microbial processes (Kele et al, 2008;García-del-Cura et al, 2014). On the other hand, changes in δ 18 O values can also reflect the effect of evaporation, temperature of water and, at the time of precipitation, degassing of CO 2 and/or groundwater inflow (Chafetz and Lawrence, 1994;Valero-Garcés et al, 2001;Kele et al, 2008).…”
Section: Discussion Of Stable Isotope Datamentioning
confidence: 99%
See 1 more Smart Citation
“…These deposits can be classified as thermogene deposits following Pentecost (2005) classification. δ 13 C values in hot-water travertine deposits are mainly controlled by physical (CO 2 degassing or water temperature) and microbial processes (Kele et al, 2008;García-del-Cura et al, 2014). On the other hand, changes in δ 18 O values can also reflect the effect of evaporation, temperature of water and, at the time of precipitation, degassing of CO 2 and/or groundwater inflow (Chafetz and Lawrence, 1994;Valero-Garcés et al, 2001;Kele et al, 2008).…”
Section: Discussion Of Stable Isotope Datamentioning
confidence: 99%
“…In Berrazales deposit changes in evaporation, water temperature or degassing were probably not significant because the small size of the deposit did not allow water to reequilibrate. CO 2 removal and subsequent variations in δ 13 C values in Berrazales travertine could occur due to biological processes, such as respiration or microbial photosynthesis (García-del-Cura et al, 2014). Microbes consumed preferably the lighter carbon isotope, enriching water and the precipitated calcite in the heaviest isotope, as shown by heavy δ 13 C values and high Mg content on micrite/microsparite, precipitated under the influence of EPS.…”
Section: Discussion Of Stable Isotope Datamentioning
confidence: 99%
“…Hence, in modern and experimental studies disordered (proto)dolomite formation has been observed, in various contexts, in waters from fresh to saline. Examples include: (i) actively photosynthesizing microbial mats (García‐del‐Cura et al ., ); (ii) in association with extracellular polymeric substances with living or dead microbiotas (Bontognali et al ., ); and (iii) in artificial analogues containing carboxyl groups (Roberts et al ., ). Dolomite can form in sulphate‐rich water (Sánchez‐Román et al ., ), although its formation can be enhanced by sulphate‐reducing bacteria (Wacey et al ., ; Krause et al ., ), and is promoted by the presence of sulphide ions (Zhang et al ., ).…”
Section: Chemical Sedimentology: Atmospheric and Hydrospheric Signalsmentioning
confidence: 99%
“…Several studies have recorded an increase in the carbon isotopic signal linked to photosynthetic effects (Pentecost and Spiro, 1990;Lojen et al, 2004;García-del-Cura et al, 2014), but other studies have not observed this relation (Shiraishi et al, 2008). In this study, framestone of bryophyte (moss) facies present the lightest δ 13 C values, which could be related to purely physicochemical precipitation.…”
Section: Discussionmentioning
confidence: 44%